(untitled) (Journal of the College of Basic Education, 2023)
The teaching methods in most countries of the world, especially the developing ones, have taken a large part and become one of the most importantThings to be studied and to know the obstacles to their application so that researchers can develop successful solutions to mitigate the problemThis phenomenon, which sometimes results in a major failure in the scientific level of students, because the shortcomings and weaknesses in thisMethods, especially in the use of modern technical means such as the computer and its capabilities represented by systems and programsapplied is very clear; In order to achieve the educational goals in all its cognitive, emotional and skill dimensions, the methodsThe successful teaching staff contributes greatly to the success of the educational process through improving the scientific level of the studentand the organization of relations between it and the study material and the surrounding environment; Teaching methods have becomeEspecially the modern ones in our time, a basic need that every student and student, regardless of his level of comprehension and acceptance.for the course.